Basalt fiber composite material capable of self-sensing damage and preparation method thereof

By modifying and introducing conductive nanofillers on the surface of the basalt fibers, the conductive hierarchical structure is constructed, and the problems of low mechanical properties and conductivity of basalt fiber composites are solved, achieving the improvement of high performance and self-perception of damage.

CN119899515AInactive Publication Date: 2025-04-29SOUTHWEST PETROLEUM UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510386374.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing basalt fiber composites have problems with insufficient mechanical properties and low conductivity in the processing of high-performance thermoplastic composites, especially because nanofillers are prone to shedding and low polymer pyrolysis temperature, which limits their use in high-performance applications.

Method used

By wrapping the surface of the basalt fibers with a diazaneone biphenyl structure polyarylethersulfone ketone coating and welding the carbon nanofibers on the coating by high temperature melting, a basalt fibers modified by the carbon nanofiber/diazazane biphenyl structure polyarylethersulfone ketone composite coating is formed, and a conductive hierarchical structure is constructed by combining graphene nanosheets and polyarylethernitrile matrix.

Benefits of technology

The mechanical properties and electrical conductivity of basalt fiber composite materials are significantly improved, the bond between the conductive nanofillers and fibers is enhanced, the nanofillers are avoided, and the material is given a self-perception function of damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899515A_ABST
    Figure CN119899515A_ABST
Patent Text Reader

Abstract

The invention discloses a damage self-sensing basalt fiber composite material and a preparation method thereof, and belongs to the technical field of fiber reinforced composite materials. The preparation method comprises the following steps: pyrolyzing chopped basalt fiber bundles to obtain desized basalt fibers; the preparation method comprises the following steps: preparing a PPESK solution containing a phthalazinone biphenyl structure and a carbon nanofiber / polyethylene glycol suspension; sequentially dipping the desized basalt fiber in the solution and the suspension to respectively obtain PPESK modified basalt fiber and basalt fiber adsorbing carbon nanofiber; carrying out heat treatment on the basalt fiber adsorbed with the carbon nanofiber, so that the carbon nanofiber is embedded into the PPESK coating to obtain the basalt fiber modified by the carbon nanofiber / PPESK composite coating; the graphene nanosheets are sequentially blended with poly (arylene ether nitrile) and basalt fibers modified by the carbon nanofiber / PPESK composite coating, and a basalt fiber composite material is obtained through hot pressing; by constructing a hierarchical structure, the mechanical property of the basalt fiber composite material is improved, and the damage self-sensing function is given to the basalt fiber composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a basalt fiber composite material capable of self-sensing damage and a preparation method thereof, belonging to the technical field of fiber-reinforced composite materials. Background Art

[0002] Basalt fiber is widely used in aerospace, oil and gas transportation, building structures, energy equipment and other fields due to its green and pollution-free, high strength-to-weight ratio, excellent mechanical properties, corrosion resistance and wear resistance. Basalt fiber composites made of basalt fiber and polymer have higher mechanical properties than glass fiber composites, lower energy consumption and manufacturing costs than carbon fiber and aramid fiber composites, and have attracted widespread attention from industry and academia. Basalt fiber has a smooth and inert surface, resulting in poor interfacial bonding strength between it and the matrix, limiting its demand for use in high-end fields.

[0003] The existing methods for modifying the surface of basalt fibers mainly include chemical vapor deposition, electrophoretic deposition, acid-base treatment, plasma treatment, silanization treatment and coating modification. Surface modification methods such as chemical vapor deposition, electrophoretic deposition, acid-base treatment, plasma treatment and silanization treatment have certain limitations. For example, chemical vapor deposition has harsh implementation conditions, and the catalysts that are difficult to remove remain on the surface of the modified basalt fibers; electrophoretic deposition has complex and tedious experimental steps; acid-base treatment, silanization treatment and plasma treatment etch and destroy the intrinsic structure of basalt fibers. At present, coating modification is regarded as an effective method for modifying the surface of basalt fibers.

[0004] The nanofiller coating is directly deposited on the surface of basalt fiber. Due to the lack of strong bonding between the nanofiller and the basalt fiber, the nanofiller is easy to fall off the surface of the basalt fiber during processing, thus limiting the reinforcement of the basalt fiber composite material. In order to increase the bonding between the nanofiller and the basalt fiber, polymers are often used as binders. However, most polymer coatings are composed of epoxy polymers, and their initial pyrolysis temperature is usually lower than 250°C, which limits their application in the processing of high-performance thermoplastic composites. In addition, a conductive composite coating composed of conductive nanofillers and polymers is coated on the surface of basalt fiber, and this method makes the basalt fiber functional. However, since the conductivity of the polymer is much lower than that of the conductive nanofiller, such a coating limits the conductivity of the modified basalt fiber composite material. In response to the above challenges, we combined the surface modification of basalt fiber and the introduction of conductive nanofillers in the matrix material, constructed a hierarchical structure consisting of fiber modification and matrix nano-reinforcement in the basalt fiber composite material, and proposed a method that can simultaneously improve the mechanical properties and damage self-sensing function of basalt fiber composite materials. Compared with other preparation methods of functional basalt fiber composite materials, the method proposed in the present invention has the characteristics of simple operation, obvious performance improvement, high economic benefit, etc. Summary of the invention

[0005] The present invention mainly overcomes the deficiencies in the prior art and proposes a method for preparing a basalt fiber composite material with damage self-sensing. The basalt fiber composite material prepared by this method has high mechanical properties as well as high electrical conductivity and excellent damage self-sensing function.

[0006] The technical solution provided by the present invention to solve the above technical problems is: a method for preparing a basalt fiber composite material with self-sensing damage, comprising the following steps: S1, placing the short chopped basalt fiber bundle in a tubular furnace for pyrolysis, cooling to room temperature, washing and drying to obtain desizing basalt fiber; S2, dissolving the poly(aryl ether sulfone ketone) containing a diazonium ketone biphenyl structure in N,N-dimethylformamide to obtain an organic solution, and ultrasonically dispersing the carbon nanofibers and polyethylene glycol in deionized water to obtain a suspension; S3, soaking the desized basalt fiber in the organic solution obtained in S2, filtering and drying, and obtaining a basalt fiber modified with a poly(aryl ether sulfone ketone) containing a diazonium ketone biphenyl structure; S4, soaking the basalt fiber modified with poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure in the suspension obtained in S2, filtering and drying, and obtaining the basalt fiber adsorbed with carbon nanofibers; S5, placing the basalt fiber adsorbed with the carbon nanofiber in a tubular furnace, heating, heat preservation, cooling, cleaning and drying, so that the carbon nanofiber on the surface of the basalt fiber is embedded in the poly(aryl ether sulfone ketone) coating containing a diazinone biphenyl structure, to obtain a basalt fiber modified with a carbon nanofiber / poly(aryl ether sulfone ketone) composite coating containing a diazinone biphenyl structure; S6. Premixing graphene nanosheets and poly(arylether nitrile) by melt premixing, adding basalt fibers modified with a carbon nanofiber / poly(arylether sulfone ketone) composite coating containing a diazinone biphenyl structure, blending, and hot pressing to obtain a basalt fiber composite material.

[0007] A further technical solution is that the length of the chopped basalt fiber bundle in step S1 is 3 mm.

[0008] A further technical solution is that the pyrolysis environment is a high-temperature oxygen-free environment, the protective gas is nitrogen, and the gas flow rate is 1 L / min.

[0009] A further technical solution is that the pyrolysis in step S1 is divided into two stages.

[0010] Furthermore, the first stage pyrolysis temperature is 250°C, the pyrolysis time is 30 minutes, and the heating rate to reach the first stage pyrolysis temperature is 5°C / min.

[0011] Furthermore, the second stage pyrolysis temperature is 400°C, the pyrolysis time is 1 hour, and the heating rate to reach the second stage pyrolysis temperature is 10°C / min.

[0012] A further technical solution is that the cooling method is natural cooling.

[0013] A further technical solution is that the concentration of the poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure in step S2 is 5-10 mg / mL.

[0014] A further technical solution is that the concentration of the carbon nanofibers is 0.3-0.5 mg / mL, and the mass ratio of the carbon nanofibers to the polyethylene glycol is 1:4.

[0015] A further technical solution is that the soaking time in step S3 is 20 minutes.

[0016] A further technical solution is that the roughness of the basalt fiber modified with poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure is 20-30 nm.

[0017] A further technical solution is that the soaking time in step S4 is 30 minutes.

[0018] A further technical solution is that the roughness of the basalt fiber adsorbed with the carbon nanofibers in step S4 is 50-65 nm.

[0019] A further technical solution is that the protective gas of the tubular furnace in step S5 is a mixed gas of argon and nitrogen.

[0020] Furthermore, the volume ratio of argon to nitrogen is 1:2, and the gas flow rate is 9 L / min.

[0021] Furthermore, ventilation is started 10 minutes before heating and nitrogen ventilation is stopped at the end of heat preservation.

[0022] A further technical solution is that the heating rate is 10°C / min.

[0023] A further technical solution is that the insulation temperature is 350° C. and the insulation time is 1 hour.

[0024] A further technical solution is that the cooling method is inert gas cooling, the inert gas is argon, and the gas flow rate is 3L / min.

[0025] A further technical solution is that the roughness of the basalt fiber modified by the carbon nanofiber / poly(aryl ether sulfone ketone) composite coating containing diazonium ketone biphenyl structure in step S5 is 40-50 nm.

[0026] A further technical solution is that the premixing and blending equipment in step S6 is a computer-controlled torque rheometer.

[0027] A further technical solution is that the mass fraction of the graphene nanosheets is 3-5wt%, and the mass fraction of the basalt fiber modified by the carbon nanofiber / polyaryl ether sulfone ketone composite coating containing diazonium phthalide biphenyl structure is 5-40wt%.

[0028] A further technical solution is that the premixing temperature is 280° C., the time is 5 minutes, and the rotation speed is 100 rpm.

[0029] A further technical solution is that the blending temperature is 300° C., the time is 10 min, and the rotation speed is 120 rpm.

[0030] The second technical problem to be solved by the present invention is to provide a damage-self-sensing basalt fiber composite material prepared by the above method.

[0031] The present invention has the following beneficial effects: (1) The present invention uses a poly(aryl ether sulfone ketone) coating containing a diazinone biphenyl structure to wrap the surface of basalt fiber, thereby repairing the surface defects of the basalt fiber while maintaining its own structure; and by high-temperature melting the poly(aryl ether sulfone ketone) coating containing a diazinone biphenyl structure, the carbon nanofiber is welded to the coating, thereby strengthening the bonding between the conductive nanofiller and the basalt fiber, and effectively preventing the conductive nanofiller from falling off during processing; and the conjugation effect between the poly(aryl ether sulfone ketone) containing a diazinone biphenyl structure, the carbon nanofiber and the poly(aryl ether nitrile) and the graphene nanosheets in the poly(aryl ether nitrile) enhances the interfacial bonding strength between the basalt fiber and the matrix, which is beneficial to the stress transfer from the matrix to the fiber, thereby improving the mechanical properties of the basalt fiber composite material.

[0032] (2) The present invention welds carbon nanofibers to the surface of basalt fibers through a phthalazinone biphenyl structure poly(arylether sulfone ketone) coating, thereby improving the roughness of the basalt fiber surface and increasing the mechanical meshing between the basalt fiber and the matrix; and, the phthalazinone biphenyl structure poly(arylether sulfone ketone) and carbon nanofibers together form a modulus transition layer between the basalt fibers and the poly(arylether nitrile) matrix, thereby slowing down the modulus mutation from basalt fibers to poly(arylether nitrile); in addition, the graphene nanosheets dispersed in the poly(arylether nitrile) play a role in passivating crack tips, hindering crack propagation and nano-enhancement, and these factors further improve the mechanical properties of the basalt fiber composite material.

[0033] (3) In the present invention, the graphene nanosheets dispersed in the polyarylethernitrile matrix and the carbon nanofibers distributed on the surface of the basalt fiber form a conductive network structure in the matrix and on the fiber surface of the basalt fiber composite material, respectively; the conductive network on the surface of the basalt fiber realizes a long-range conductive path for electrons, while the conductive network dispersed in the polyarylethernitrile matrix realizes a short-range conductive path for electrons, and the two together construct a multi-scale conductive hierarchical structure to improve the conductivity of the basalt fiber composite material; and such a conductive hierarchical structure enables the basalt fiber composite material to accurately and sensitively sense external loads and convert the received loads into electrical signal outputs, thereby giving the basalt fiber composite material a damage self-sensing function. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a preparation flow chart of the present invention; Figure 2 Scanning electron microscope images of basalt fibers modified with poly(aryl ether sulfone ketone) containing diazinone biphenyl structure and basalt fibers modified with carbon nanofiber / poly(aryl ether sulfone ketone) containing diazinone biphenyl structure composite coating; Figure 3 The roughness diagrams of basalt fibers modified with poly(aryl ether sulfone ketone) containing diazinone biphenyl structure and basalt fibers modified with carbon nanofiber / poly(aryl ether sulfone ketone) containing diazinone biphenyl structure composite coating; Figure 4 is the mechanical properties diagram of basalt fiber composites; Figure 5 is the conductivity diagram of basalt fiber composites; Figure 6 This is the damage self-sensing test diagram of basalt fiber composite material; DETAILED DESCRIPTION

[0035] The present invention will be further described below with reference to the embodiments, comparative examples and accompanying drawings.

[0036] Example 1 like Figure 1 As shown, a damage-self-sensing basalt fiber composite material of the present invention is prepared by the following steps: Step 1: Place a 3 mm long short-cut basalt fiber bundle in a tubular furnace, pyrolyze in a high temperature oxygen-free environment, cool naturally to room temperature, wash and dry, and obtain short-cut desizing basalt fibers; Among them, the protective gas is nitrogen, and the gas flow rate is 1L / min; the pyrolysis is divided into two stages, the pyrolysis temperature of the first stage is 250°C, the pyrolysis time is 30min, and the heating rate to reach the pyrolysis temperature of the first stage is 5°C / min; the pyrolysis temperature of the second stage is 400°C, the pyrolysis time is 1h, and the heating rate to reach the pyrolysis temperature of the second stage is 10°C / min.

[0037] Step 2: Dissolve 5 mg / mL of poly(aryl ether sulfone ketone) containing diazonium phthalide biphenyl structure in N,N-dimethylformamide to obtain an organic solution, and ultrasonically disperse 0.5 mg / mL of carbon nanofibers and 2 mg / mL of polyethylene glycol in deionized water to obtain a suspension.

[0038] Step 3: Soak the short-cut desizing basalt fiber in an organic solution for 20 minutes, filter and dry, and obtain basalt fiber modified with poly(aryl ether sulfone ketone) containing a diazonium phthalide biphenyl structure.

[0039] Step 4: Soak the basalt fiber modified with poly(aryl ether sulfone ketone) containing diazonium phthalide biphenyl structure in the suspension for 30 minutes, filter and dry to obtain the basalt fiber adsorbed with carbon nanofibers.

[0040] Step 5: placing the basalt fiber adsorbed with the carbon nanofiber in a tubular furnace, heating, heat preservation, cooling, washing and drying, and obtaining the basalt fiber modified with the carbon nanofiber / polyarylethersulfoneketone composite coating containing diazonium phthalide biphenyl structure; Among them, the protective gas of the tubular furnace is a mixed gas of argon and nitrogen with a volume ratio of 1:2, the gas flow rate is 9L / min, ventilation starts 10min before heating, and nitrogen ventilation is stopped after the insulation is completed; the heating rate is 10℃ / min; the insulation temperature is 350℃, and the insulation time is 1h; the cooling method is inert gas cooling, the inert gas is argon, and the gas flow rate is 3L / min.

[0041] Step 6: Use a computer-controlled torque rheometer to melt-premix graphene nanosheets with a mass fraction of 4 wt% and poly(arylether nitrile) at a temperature of 280°C and a rotation speed of 100 rpm for 5 minutes, add basalt fibers modified with a composite coating of carbon nanofibers / poly(arylether sulfone ketone) containing a diazonium phthalide biphenyl structure with a mass fraction of 30 wt%, blend at a temperature of 300°C and a rotation speed of 120 rpm for 10 minutes, and hot press to obtain a basalt fiber composite material.

[0042] Comparative Example 1 Step 1: Place a 3 mm long short-cut basalt fiber bundle in a tubular furnace, pyrolyze in a high temperature oxygen-free environment, cool naturally to room temperature, wash and dry, and obtain short-cut desizing basalt fibers; Among them, the protective gas is nitrogen, and the gas flow rate is 1L / min; the pyrolysis is divided into two stages, the pyrolysis temperature of the first stage is 250°C, the pyrolysis time is 30min, and the heating rate to reach the pyrolysis temperature of the first stage is 5°C / min; the pyrolysis temperature of the second stage is 400°C, the pyrolysis time is 1h, and the heating rate to reach the pyrolysis temperature of the second stage is 10°C / min.

[0043] Step 2: Use a computer-controlled torque rheometer to melt-premix the polyarylethernitrile at a temperature of 280°C and a rotation speed of 100 rpm for 5 minutes, add 30 wt% of short-cut desizing basalt fiber, blend at a temperature of 300°C and a rotation speed of 120 rpm for 10 minutes, and hot press to obtain a short-cut desizing basalt fiber / polyarylethernitrile composite material.

[0044] The basalt fiber modified with poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure prepared in step 1, step 2 and step 3 of Example 1 and the basalt fiber modified with carbon nanofiber / poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure composite coating prepared in step 1, step 2, step 3, step 4 and step 5 of Example 1 were observed for microscopic morphology. The results are as follows: Figure 2 shown.

[0045] Figure 2The rough surface morphology of basalt fibers modified with poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure and basalt fibers modified with carbon nanofibers / poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure composite coating was revealed. The surface of basalt fibers modified with carbon nanofibers / poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure composite coating formed a network structure constructed by the interaction of carbon nanofibers.

[0046] The surface roughness of the basalt fiber modified with poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure prepared in step 1, step 2 and step 3 of Example 1 and the basalt fiber modified with the carbon nanofiber / poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure composite coating prepared in step 1, step 2, step 3, step 4 and step 5 of Example 1 were characterized. The results are as follows: Figure 3 shown.

[0047] Figure 3 It was revealed that the roughness of the basalt fiber modified with poly(aryl ether sulfone ketone) containing diazonium phthalide biphenyl structure was 22nm, and the roughness of the basalt fiber modified with the carbon nanofiber / poly(aryl ether sulfone ketone) containing diazonium phthalide biphenyl structure composite coating was 45nm.

[0048] The basalt fiber composite material prepared in Example 1 and the short-cut desizing basalt fiber / polyarylethernitrile composite material prepared in Comparative Example 1 were tested for bending properties. The results are as follows: Figure 4 shown.

[0049] Figure 4 It was revealed that the flexural strength of the chopped desizing basalt fiber / polyarylethernitrile composite material was 116MPa, and the flexural strength of the basalt fiber composite material was 169MPa, indicating that the flexural properties of the basalt fiber composite material have been effectively improved.

[0050] The conductivity of the basalt fiber composite material prepared in Example 1 and the short-cut desizing basalt fiber / polyarylethernitrile composite material prepared in Comparative Example 1 were tested. The results are as follows: Figure 5 shown.

[0051] Figure 5 The conductivity of chopped desizing basalt fiber / poly(arylene ether nitrile) composites was revealed to be 6×10 -12 S / m, while the conductivity of basalt fiber composite material reaches 8×10 -4 S / m, this is because a conductive hierarchical structure constructed by a long-range conductive network on the fiber surface and a short-range conductive network in the matrix is ​​formed inside the basalt fiber composite material, which effectively improves the electrical conductivity of the basalt fiber composite material.

[0052] The basalt fiber composite material prepared in Example 1 was subjected to a unidirectional bending test in combination with electrical signal and acoustic emission signal equipment. The results are as follows: Figure 6 shown.

[0053] Figure 6 The damage self-sensing function of basalt fiber composites was revealed. According to the stress-strain curve, stress-relative resistance change (ΔR / R 0 ) curves and acoustic emission signals, the entire bending process can be divided into three stages: elastic stage (0-1.2%), damage stage (1.2-2.5%), and fracture stage (2.5-2.6%).

[0054] When the basalt fiber composite is in the elastic stage (0-1.2%), the basalt fiber composite and its internal conductive network undergo elastic deformation. At this time, the stress and ΔR / R 0 It increases linearly with strain and no acoustic emission signal is generated.

[0055] When the strain is 1.2-2.5%, the basalt fiber composite material is in the damage stage. At this stage, the stress growth rate of the basalt fiber composite material decreases, and the acoustic emission signal appears, indicating that damage has occurred inside it; and as the strain increases, the damage expands. The generation and expansion of damage continuously destroys the conductive network in the basalt fiber composite material, so that ΔR / R 0 Growing exponentially.

[0056] When the strain of the basalt fiber composite material is 2.5-2.6%, it is in the fracture stage. As the strain continues to increase, the internal damage rapidly expands and penetrates the entire basalt fiber composite material, causing the conductive network to be disconnected, which is expressed as ΔR / R 0 It increases from exponential to infinity until the basalt fiber composite material breaks.

[0057] These results show that the basalt fiber composite material prepared in Example 1 has high mechanical properties and damage self-sensing function.

[0058] The above description is not intended to impose any form of limitation on the present invention. Although the present invention has been disclosed through the above embodiments, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a damage-sensitive basalt fiber composite material, characterized in that: The following steps are involved: S1, placing the short chopped basalt fiber bundle in a tubular furnace for pyrolysis, cooling to room temperature, washing and drying to obtain desizing basalt fiber; S2, dissolving the poly(aryl ether sulfone ketone) containing a diazonium ketone biphenyl structure in N,N-dimethylformamide to obtain an organic solution, and ultrasonically dispersing the carbon nanofibers and polyethylene glycol in deionized water to obtain a suspension; S3, soaking the desized basalt fiber in the organic solution obtained in S2, filtering and drying, and obtaining a basalt fiber modified with a poly(aryl ether sulfone ketone) containing a diazonium ketone biphenyl structure; S4, soaking the basalt fiber modified with poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure in the suspension obtained in S2, filtering and drying, and obtaining the basalt fiber adsorbed with carbon nanofibers; S5, placing the basalt fiber adsorbed with the carbon nanofiber in a tubular furnace, heating, heat preservation, cooling, cleaning and drying, so that the carbon nanofiber on the surface of the basalt fiber is embedded in the poly(aryl ether sulfone ketone) coating containing a diazinone biphenyl structure, to obtain a basalt fiber modified with a carbon nanofiber / poly(aryl ether sulfone ketone) composite coating containing a diazinone biphenyl structure; S6. Premixing graphene nanosheets and poly(arylether nitrile) by melt premixing, adding basalt fibers modified with a carbon nanofiber / poly(arylether sulfone ketone) composite coating containing a diazinone biphenyl structure, blending, and hot pressing to obtain a basalt fiber composite material.

2. The method for preparing a damage-sensitive basalt fiber composite material according to claim 1, characterized in that: The length of the chopped basalt fiber bundle in step S1 is 3 mm; the pyrolysis environment is a high-temperature oxygen-free environment, the protective gas is nitrogen, and the gas flow rate is 1 L / min.

3. The method for preparing a damage-sensitive basalt fiber composite material according to claim 1, characterized in that: The pyrolysis in step S1 is divided into two stages, the pyrolysis temperature of the first stage is 250°C, the pyrolysis time is 30 minutes, and the heating rate to reach the pyrolysis temperature of the first stage is 5°C / min; the pyrolysis temperature of the second stage is 400°C, the pyrolysis time is 1 hour, and the heating rate to reach the pyrolysis temperature of the second stage is 10°C / min; the cooling method is natural cooling.

4. The method for preparing a damage-sensitive basalt fiber composite material according to claim 1, characterized in that: The concentration of the poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure in step S2 is 5-10 mg / mL; the concentration of the carbon nanofiber is 0.3-0.5 mg / mL, and the mass ratio of the carbon nanofiber to the polyethylene glycol is 1:

4.

5. The method for preparing a damage-sensitive basalt fiber composite material according to claim 1, characterized in that: The immersion time in step S3 is 20 minutes; the roughness of the basalt fiber modified with poly(aryl ether sulfone ketone) containing diazonium ketone biphenyl structure in step S3 is 20-30nm; the immersion time in step S4 is 30 minutes; the roughness of the basalt fiber adsorbed with carbon nanofibers in step S4 is 50-65nm.

6. The method for preparing a damage-sensitive basalt fiber composite material according to claim 1, characterized in that: In step S5, the protective gas of the tubular furnace is a mixed gas of argon and nitrogen, wherein the volume ratio of argon to nitrogen is 1:2, the gas flow rate is 9 L / min, ventilation starts 10 minutes before heating, and nitrogen ventilation is stopped after the insulation is completed.

7. The method for preparing a damage-sensitive basalt fiber composite material according to claim 1, characterized in that: In the step S5, the heating rate is 10°C / min; the insulation temperature is 350°C, and the insulation time is 1h; the cooling method is inert gas cooling, the inert gas is argon, and the gas flow rate is 3L / min.

8. The method for preparing a damage-sensitive basalt fiber composite material according to claim 1, characterized in that: In the step S5, the roughness of the basalt fiber modified by the carbon nanofiber / poly(aryl ether sulfone ketone) composite coating containing diazonium ketone biphenyl structure is 40-50 nm.

9. The method for preparing a damage-sensitive basalt fiber composite material according to claim 1, characterized in that: The premixing and blending equipment in step S6 is a computer-controlled torque rheometer; the mass fraction of the graphene nanosheets is 3-5wt%, and the mass fraction of the basalt fiber modified with the carbon nanofiber / polyaryl ether sulfone ketone composite coating containing diazonium phthalide biphenyl structure is 5-40wt%; the premixing temperature is 280°C, the time is 5min, and the rotation speed is 100rpm; the blending temperature is 300°C, the time is 10min, and the rotation speed is 120rpm.

10. A basalt fiber composite material capable of self-sensing damage, characterized in that: The basalt fiber composite material with damage self-sensing is prepared according to the preparation method of any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of conductive basalt fiber material

    CN108218216A

  • Preparation method of flexible conductive polymer composite material, pressure sensor and matrix pressure sensor

    CN111452274A

  • Preparation method of basalt fiber composite material with damage self-sensing and temperature-sensitive behaviors

    CN117264401A

  • Method for preparing composite material by constructing high-temperature-resistant rigid-flexible structure with synergistic enhancement effect on fiber surface

    CN117820685A

  • Preparation method of basalt fiber high-temperature-resistant sensor

    CN118009871A